‘An Empirical Investigation of the Relationships among a Consumer’s Personal Values, Ethical Ideology and Ethical Beliefs’ - Steenhaut, Sarah (Journal of business ethics, 2006)
This study provides an additional partial test of the Hunt–Vitell theory [1986, Journal of Macromarketing, 8, 5–16; 1993, ‘The General Theory of Marketing Ethics: A Retrospective and Revision’, in N. C. Smith and J. A. Quelch (eds.), Ethics in Marketing (Irwin Inc., Homewood), pp. 775–784], within the consumer ethics context. Using structural equation modeling, the relationships among an individual’s personal values (conceptualized by the typology of Schwartz [1992, ‘Universals in the Content and Structure of Values: Theoretical Advances and Empirical Tests in 20 Countries’, in M. P. Zanna (ed.), Advances in Experimental Social Psychology (Vol. 25, Academic Press, Orlando), pp. 1–65] ethical ideology and ethical beliefs are investigated. The validity of the model is assessed in a two-step procedure. First, a measurement model of constructs is tested for key validity dimensions. Next, the hypothesized causal relationships are examined in several path models, comparing no mediation, partial and complete mediation of ethical ideology. The empirical results indicate that individual differences in value priorities (resultant conservation and resultant self-enhancement) directly and indirectly (through idealism) influence the judgment of ethically questionable consumer practices. These findings may significantly contribute to the theoretical understanding of ethical decision-making.